Pengaruh Price Perception Terhadap Repurchase Intention Fore Coffee Galuh Mas Karawang (Studi Pada Generasi Z) - Novia, Rahmah; Sudrajat, Ajat (Universitas Pahlawan Tuanku Tambusai, 2024)
This study was conducted with the aim of determining the Influence of Price Perception on Repurchase Intention Fore Coffee Galuh Mas Karawang (Case Study on Generation Z). The technique used to determine the sample for this study was purposive sampling. The research method used was a quantitative approach with analysis using simple linear regression analysis. The results of the study showed that price perception partially had an effect on repurchase intention.